Reliable Change Estimates for Assessing Recovery From Concussion Using the ANAM4 TBI-MIL. Issue 5 (September 2016) - Haran, F. J.; Alphonso, Aimee L.; Creason, Alia; Campbell, Justin S.; Johnson, Dagny; Young, Emily; Tsao, Jack W.
Abstract : Objective: To establish the reliable change parameters for the Automated Neuropsychological Assessment Metrics (ANAM) using a healthy normative sample of active duty service members (SMs) and apply the parameters to sample of recently deployed SMs. Methods: Postdeployment neurocognitive performance was compared in 1893 US Marines with high rates of combat exposure during deployment. Of the sample, 289 SMs had data for 2 predeployment assessments and were used as a normative subsample and 502 SMs had data for predeployment and postdeployment assessments and were used as a deployed subsample. On the basis of self-report, the deployed subsample were further classified as concussed ( n = 238) or as nonconcussed controls ( n = 264). Reliable change parameters were estimated from the normative sample and applied data for both deployed groups. Postdeployment performance was quantified using a general linear model (2 group × 2 time) multivariate analysis of variance with repeated measures. Results: Both deployed groups demonstrated a pattern of meaningful decreases in performance over time. Conclusions: Information from this effort, specifically the reliable change parameters and the base rates of reliable decline, can be used to assist with the identification of postdeployment cognitive issues.